Discovery of GNE-502 as an orally bioavailable and potent degrader for estrogen receptor positive breast cancer. (15th October 2021) - Zbieg, Jason R.; Liang, Jun; Li, Jun; Blake, Robert A.; Chang, Jae; Friedman, Lori; Goodacre, Simon; Hartman, Steven J.; Rei Ingalla, Ellen; Kiefer, James R.; Kleinheinz, Tracy; Labadie, Sharada; et al.
Graphical abstract: Abstract: Fulvestrant is an FDA-approved drug with a dual mechanism of action (MOA), acting as a full antagonist and degrader of the estrogen receptor protein. A significant limitation of fulvestrant is the dosing regimen required for efficacy. Due to its high lipophilicity and poor pharmacokinetic profile, fulvestrant needs to be administered through intramuscular injections which leads to injection site soreness. This route of administration also limits the dose and target occupancy in patients. We envisioned a best-in-class molecule that would function with the same dual MOA as fulvestrant, but with improved physicochemical properties and would be orally bioavailable. Herein we report our progress toward that goal, resulting in a new lead GNE-502 which addressed some of the liabilities of our previously reported lead molecule GNE-149.